PEMIKIRAN ABDUL MANNAN TENTANG EKONOMI ISLAM - Herza Ayu Menita (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2017)
According M. Mannan that distinguishes the Islamic economy and other modern economic systems, he argues, is that within an Islamic framework, prosperity and economic prosperity are the means of achieving spiritual and moral goals. Therefore, he proposes the modification of conventional Neo-Classical economic theory and its tools to realize changes in value orientation, institutional arrangements and objectives achieved. Muhammad A.Mannan considers that the concept of development in Islam has advantages over modern concepts of development. The context of economic development planning, fiscal policy design refers to the policy made by the government to direct a country's economy through government expenditures and revenues (in the form of taxes). Mannan's opinion in the concept of Islamic economy, fiscal policy aims to develop a society based on the distribution of balanced wealth by placing material and spiritual values at the same level.